The Garden of Evaluation Approaches Visualization - Bianca Montrosse-Moorhead; Daniela Schröter; Lyssa Wilson Becho (The Evaluation Center at Western Michigan University, 2024)
Background: The Garden of Evaluation Approaches (Montrosse-Moorhead, et al., 2024a) maps evaluation approaches against eight dimensions of practice and situates them in their philosophical orientations and methodological dispositions. Purpose: The Garden's guiding question is: How do evaluation approaches compare in terms of dimensions that facilitate use and application? Primary intended users are evaluation practitioners, and secondary intended users include ecosystem actors (e.g., clients, program participants, funders), educators, researchers, and theoreticians. Setting: Not applicable. Intervention: Not applicable. Research Design: Exploratory sequential mixed methods. Data Collection and Analysis: Data collection and analysis included locating and reading primary sources for each evaluation approach. One team member thematically coded each source for evidence of an approach's stance on the eight dimensions of practice, its' philosophical orientation and methodological disposition, and steps for implementing the approach in practice. This qualitative evidence was used to generate ordinal ratings for the eight dimensions using a rating scale developed by the team, and to classify the approaches' philosophical orientation and methodological disposition. Drafts of handouts summarizing qualitative and quantitative data were reviewed by the two other team members, with dialogue and deliberation among all members used to come to consensus. Findings: The first iteration of the Garden includes seven approaches: fourth generation evaluation, made in Africa, nation-to-nation evaluation, practical participatory evaluation, sistematización de experiencias, theory-driven evaluation, and transformative participatory evaluation. Each approach is represented as a flower within the Garden, with each petal corresponding to the approaches' stance on one of the eight dimensions of practice. The colors of the flowers represent the underlying philosophical foundation of the approach. The pattern within the central disc of each flower represents the methodological disposition encouraged by the approach. Summaries of the empirical mixed-method analysis are made transparent in supporting handouts. Future work will grow flowers for additional approaches and continue to map out the Garden.